FLT3-ITDs Instruct a Myeloid Differentiation and Transformation Bias in Lymphomyeloid Multipotent Progenitors - Adam J. Mead; Shabnam Kharazi; Deborah Atkinson; Iain Macaulay; Christian Pecquet; Stephen Loughran; Michael Lutteropp; Petter Woll; Onima Chowdhury; Sidinh Luc; Natalija Buza-Vidas; Helen Ferry; et al. (Cell Reports, 2013)
Whether signals mediated via growth factor receptors (GFRs) might influence lineage fate in multipotent progenitors (MPPs) is unclear. We explored this issue in a mouse knockin model of gain-of-function Flt3-ITD mutation because FLT3-ITDs are paradoxically restricted to acute myeloid leukemia even though Flt3 primarily promotes lymphoid development during normal hematopoiesis. When expressed in MPPs, Flt3-ITD collaborated with Runx1 mutation to induce high-penetrance aggressive leukemias that were exclusively of the myeloid phenotype. Flt3-ITDs preferentially expanded MPPs with reduced lymphoid and increased myeloid transcriptional priming while compromising early B and T lymphopoiesis. Flt3-ITD-induced myeloid lineage bias involved upregulation of the transcription factor Pu.1, which is a direct target gene of Stat3, an aberrantly activated target of Flt3-ITDs, further establishing how lineage bias can be inflicted on MPPs through aberrant GFR signaling. Collectively, these findings provide new insights into how oncogenic mutations might subvert the normal process of lineage commitment and dictate the phenotype of resulting malignancies.